Frontiers in colorectal surgery - Phillips, Robin K. S.; Clark, Sue (Tfm Pub., 2005)
Reviews issues considered to be of interest to qualified consultant colorectal surgeons and those performing general surgery with an interest in colorectal surgery. This book covers frontiers in neoplasia, inflammatory bowel disease, and anal disorders and management.